2012
DOI: 10.1097/hjh.0b013e3283581a64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron restriction on renal damage and mineralocorticoid receptor signaling in a rat model of chronic kidney disease

Abstract: Taken together, these data uncover a novel effect of iron restriction on renal damage and hypertension through the inhibition of renal mineralocorticoid receptor signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 25 publications
6
39
0
Order By: Relevance
“…The transcriptional expression of SGK-1 has been previously reported to be downregulated by iron restriction in rat intestine (Marzullo et al 2004) and kidney of chronic kidney disease in a rat model (Naito et al 2012). Here, we consistently observed that iron restriction by the iron cheater BP represses the expression of SGK-1::GFP (MQD862, N2;Psgk1::sgk-1::gfp) in C. elegans ( Figure S5).…”
Section: Discussionsupporting
confidence: 79%
“…The transcriptional expression of SGK-1 has been previously reported to be downregulated by iron restriction in rat intestine (Marzullo et al 2004) and kidney of chronic kidney disease in a rat model (Naito et al 2012). Here, we consistently observed that iron restriction by the iron cheater BP represses the expression of SGK-1::GFP (MQD862, N2;Psgk1::sgk-1::gfp) in C. elegans ( Figure S5).…”
Section: Discussionsupporting
confidence: 79%
“…We have previously demonstrated that iron is involved in the pathophysiology of hypertension and chronic kidney disease. 6,9,22,23 Moreover, these reports have shown that dietary IR attenuates the progression of cardiovascular remodeling and oxidative stress. We, therefore, hypothesized that iron is also involved in the pathophysiology of AAA and dietary IR could inhibit AAA formation via suppression of oxidative stress.…”
mentioning
confidence: 99%
“…8 Also, we have previously shown that iron accumulation and TfR1 expression are increased in the renal tubules of rats with CKD. 9 Generally, iron is transported into cells through TfR1. TfR1 expression is normally upregulated under low-iron conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, we have previously reported that dietary iron restriction prevents the development of hypertension and proteinuria in rats with CKD. 9 In that study, renal mineralocorticoid receptor (MR) expression in the nuclear fraction was increased in CKD rats as compared with the controls, whereas circulating aldosterone levels were decreased in CKD rats compared with the controls. In general, it is widely accepted that exogenous high aldosterone and salt induce renal injury.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation